2017
DOI: 10.1007/s00441-017-2591-2
|View full text |Cite
|
Sign up to set email alerts
|

Calpain inhibition prevents flotillin re-ordering and Src family activation during capacitation

Abstract: Prior to fertilization, mammalian sperm undergo several molecular, biochemical and physiological changes in a process termed capacitation. However, the mechanisms explaining the involvement of cytoskeletal remodeling and membrane re-ordering in each process prior to fertilization remain poorly understood. We found that the migration of both flotillin microdomains and Src family kinases towards the apical ridge of guinea pig sperm occurs under capacitating conditions. This re-ordering is associated with spectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 89 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Spermatozoa were capacitated (60 minutes) in the absence and presence of NSC23766 (100 μM). In other studies, we have defined the different fluorescent patterns observed when spermatozoa are stained with CTC: pattern F for noncapacitated spermatozoa, pattern B for capacitated spermatozoa, and AR pattern for sperm that have experienced AR . These patterns are shown in Figure B.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Spermatozoa were capacitated (60 minutes) in the absence and presence of NSC23766 (100 μM). In other studies, we have defined the different fluorescent patterns observed when spermatozoa are stained with CTC: pattern F for noncapacitated spermatozoa, pattern B for capacitated spermatozoa, and AR pattern for sperm that have experienced AR . These patterns are shown in Figure B.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, we have defined the different fluorescent patterns observed when spermatozoa are stained with CTC: pattern F for noncapacitated spermatozoa, pattern B for capacitated spermatozoa, and AR pattern for sperm that have experienced AR. 12,23 These patterns are shown in Figure 2B. After 60 minutes of capacitation, patterns B and AR increased significantly in comparison with noncapacitated spermatozoa (P = .001 and P = .002, respectively; Figure 2B).…”
Section: Rac1 Is Involved In Capacitation and Armentioning
confidence: 89%
See 3 more Smart Citations